The referendum and other essays on constitutional politics - Qvortrup, Matt (Oxford, UK [Chicago, Illinois] Hart Publishing, 2019)
"Until recently, referendums were little used and discussed, particularly in the political landscape of the United Kingdom. After the seismic impact of the Brexit referendum, they have come to the fore as a mechanism with the potential to disrupt the status quo and radically change political direction. This book looks at the historical development of the referendum, its use in different jurisdictions, and the types of constitutional questions it seeks to address. Written in an engaging style, this offers a clear, objective overview of this important political and constitutional tool"-- Provided by publishe
The referendum : Non basta più -- The world history of referendums, 1400-2018 -- Plebiscites in dictatorships : voting as a signifiant of total control -- The law and politics of independence referendums -- Consociationalism and direct democracy : direct democracy and elite accommodation -- The stupidity of the people or the wisdom of common folks? Direct democracy and better public policies? -- Prediction or prophecy : forecasting the outcome of EU referendums -- Brexit as an inelastic good -- Comparative constitution making : an introduction -- The consent of the governed : the American Revolution and the US Constitution -- Total recall : revocation of electoral mandates -- Final thought
Keywords: Referendu; Constitutional histor; Direct democrac; Political participatio